Implementasi Kurikulum Outcome Based Education (Obe) Dalam Sistem Pendidikan Tinggi Di Era Revolusi Industri 4.0 - Muzakir, Muchammad Ibnu; Susanto (Edukasiana: Journal of Islamic Education, 2023)
Abstract The purpose of this study was to determine the strategies, influencing factors, obstacles and challenges of implementing the Outcome Based Education (OBE) curriculum in the Higher Education System in the Industrial Revolution Era 4.0. The method used in this study is a library research method with a descriptive qualitative approach. Data collection techniques were carried out using library research techniques, literature reviews and research journals. There are strategies that can be implemented the OBE curriculum in the Higher Education System in the Industrial Revolution Era 4.0, namely curriculum reconstruction by compiling the structure of learning objectives, graduate learning outcomes and learning outcomes in the syllabus and analyzing the teaching and learning process. The learning system can be done with blended learning. Improving literacy 4.0 (data literacy, technological literacy, human literacy among students) and implementing the learning phase and learning space. And there are factors that influence the successful implementation, namely a learning method that consists of turning on student discussion spaces outside the classroom, modern and multidisciplinary learning, factors Furthermore, there is also academic freedom and the role of lecturers and students who greatly support the successful implementation of the OBE curriculum. Furthermore, there are 12 challenges in implementing OBE, namely the challenge of accepting OBE, paradigm shifting, maintaining the quality of education, restructuring results and assessment techniques, OBE as a top priority, design down approach, impact on students with special needs, teacher's role, learning responsibilities, break typecast, waves of opposition, and perceptions of students and teachers. Keywords: Outcome Based Education (OBE), Industrial Revolution 4.0, Higher Education System.